Transformasi Rekonsiliasi Bank: Mengintegrasikan RFID untuk Otomasi Transaksi Kartu dalam Sistem Penerimaan Kas - Suyatna, Nano (Jurnal Accounting Information System (AIMS), 2025)
This study aims to design a cash receipt system based on the integration of Radio Frequency Identification (RFID) and Electronic Data Interchange (EDI) technologies, supporting the automation of transactions and data reconciliation in the financial sector. The primary focus is on applying a Data Flow Diagram (DFD) to model the flow of data. This research adopts a system design approach using DFD to identify data flows from RFID devices, banks, and the cash receipt system. The analysis illustrates the processes of data collection, data transmission through EDI, and bank reconciliation. The DFD for RFID and EDI integration enables the automatic collection of transaction data and structured data transmission. The DFD further details data verification by the cash receipt system module and automatic reconciliation between data from RFID and banks. Findings indicate that this integration enhances operational efficiency, minimizes human errors, and supports card-based transaction automation. The system has the potential to significantly improve efficiency and accuracy in financial transaction management, with substantial implications for the implementation of Industry 4.0 in the financial sector.